Adopsi Inovasi Sistem Informasi Manajemen Rumah Sakit (SIMRS) Di UPT RSUD Kabupaten Kepulauan Meranti - Apry Rifaldi; Dedi Kusuma Habibie (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2024)
UPT RSUD Meranti Islands Regency is a regional hospital that provides services in the medical field, one of the services is outpatient services. Adoption of Innovation in SIMRS providing outpatient services has improved but is not yet optimal. This research aims to determine the adoption of Hospital Management Information System (SIMRS) innovations at the UPT RSUD Meranti Islands Regency. In this study, researchers used 5 criteria for measuring Innovation Adoption by Rogers with five indicators, namely Knowledge, Persuasion, Decision Making, Implementation, and Confirmation. This research uses qualitative methods with data collection techniques based on observation, interviews and documentation. The results of this research show that the adoption of innovation in outpatient services at the UPT RSUD Meranti Islands Regency has not been optimal but is considered to have improved from before. The hospital has made new breakthroughs such as online registration and conducting evaluations every month. It is hoped that outpatient services can continue to improve so that they can get satisfaction from patients. Factors that become obstacles in implementing the Adoption of Hospital Management Information System Innovation (SIMRS) are limited internet connection, untrained human resources and difficulty using the system.